Nanobiomaterials in the Management of Oral Biofilms - Sruthi Venu; Reshma Suvarna; Sharan S Sargod; Sham S Bhat; H T Ajay Rao (Journal of Multidisciplinary Dental Research)
The oral cavity inhabits diverse microorganisms with members of all age groups including children being associated with oral infections. Bacteria being the principle component of this resident microflora along with the diverse group of other species reflect the wide range of viscerously derived nutrients, the heterogenous habitats for colonization contributing to the survival of the biofilm. Biofilms constitute surface- adherent communities of microorganisms like Streptococcus mutans along with other bacterial species embedded in an extracellular matrix material. The commensal relationship between the host and the microflora can be disrupted in numerous ways, resulting in compromised oral health causing conditions like dental caries and endodontic infections, gingival and periodontal conditions, oral candidiasis and peri-implantitis. Biofilm-related infections prove to be a major threat from both an economical and health perspective. Innovative treatment options remain limited despite of advancements in understanding the mechanisms of biofilm formation. The concept of nanotechnology is based on controlling atoms on an individual basis and creating structures less than 100 nm (10_7 m) in size thereby greatly influencing the properties. Incorporation of metals and other nanoparticles with polymers and coating of surfaces provide antimicrobial and anti-adhesive benefits within the oral cavity. Therefore, this paper seeks to throw light into the current advancements in nanoparticle mediated treatment approaches of oral biofilms and its future implications in pediatric dentistry. Keywords: Biofilm, Oral Cavity, Metal Oxides, Nanoparticles, Reactive Oxygen Species, Antibiofilm Efficacy